2022
DOI: 10.1098/rspb.2021.2100
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA content in eggs as a maternal effect

Abstract: The transmission of detrimental mutations in animal mitochondrial DNA (mtDNA) to the next generation is avoided by a high level of mtDNA content in mature oocytes. Thus, this maternal genetic material has the potential to mediate adaptive maternal effects if mothers change mtDNA level in oocytes in response to their environment or body condition. Here, we show that increased mtDNA abundance in mature oocytes was associated with fast somatic growth during early development but at the cost of increased mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Body weight of these offspring was shown to be influenced by the dam acclimation temperature, probably induced by the different mitochondria respiration capacities [65]. Still, in the sticklebacks, warmer temperatures experienced by dam were shown to influence mitochondrial DNA level in oocytes [66]. Mitochondrial DNA level in oocytes was shown to significantly affect growth and mortality at least in the first week of life [66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body weight of these offspring was shown to be influenced by the dam acclimation temperature, probably induced by the different mitochondria respiration capacities [65]. Still, in the sticklebacks, warmer temperatures experienced by dam were shown to influence mitochondrial DNA level in oocytes [66]. Mitochondrial DNA level in oocytes was shown to significantly affect growth and mortality at least in the first week of life [66].…”
Section: Discussionmentioning
confidence: 99%
“…Still, in the sticklebacks, warmer temperatures experienced by dam were shown to influence mitochondrial DNA level in oocytes [66]. Mitochondrial DNA level in oocytes was shown to significantly affect growth and mortality at least in the first week of life [66]. It is therefore possible that maternal intergenerational plasticity could impact other traits such as acute hyperthermia resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal effect is defined as the causal influence of the maternal phenotype on the offspring phenotype in other ways than the direct transmission of genetic information (Mousseau & Fox, 1998; Wolf & Wade, 2009). Mechanisms of maternal effects are diverse and include the direct transfer of maternal resources and other substances, such as hormones, antioxidants, antibodies, transcripts (mRNA) and even mitochondrial DNA (mtDNA) copies (Boulinier & Staszewski, 2008; Fernández‐Díez et al, 2016; Groothuis et al, 2019; Kim et al, 2022; Morales, 2020). Studying how the maternal allocation changes with maternal age at reproduction should help our understanding of maternal effect senescence.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of a teleost fish, we have shown that the abundance of mtDNA copies in mature oocytes is also an important maternal trait that influences offspring growth and viability during embryogenesis and changes in response to the environment experienced by the mother (Kim et al, 2022). The level of mtDNA content increases by replication during the maturation of oocytes (Otten et al, 2016), and this process may be influenced by the body condition or ageing of the mother.…”
Section: Introductionmentioning
confidence: 99%